Organizational commitment and governance for supply chain success in Christian Protestant Churches in Bali - I Made Dwi Adnyana; Wayan Gede Supartha; I Gede Riana; Ida Bagus Ketut Surya (International Journal of Supply Chain Management, 2020)
Abstract-Commitment is an important component for successful durable relations that are a constituent of the implementation of Supply Chain Management. This study aims to develop organizational commitment for supply chain strategies success. The current research was conducted in the churches in Bali, Bukit Dua Prayer Church of Nusa Dua and Immanuel Tabanan. A total of 1,045 members of the congregation were gathered by the assembly and congregants. Thereafter, they were relegated to active assemblies and congregations, resulting in a total of 120 assemblies and administrators, for a total of 120 respondents. Inferential analysis in this study uses a structural equation model based on variance or component-based structural equation models, known as partial least squares. Results are as follows. Misbehaviour of church management has a positive and significant effect on conflict. That is, the stronger the misbehaviour management, the more conflict in Bukit Doa Nusa Dua Congregation and Immanuel Tabanan Gongregation. Religious social values do not affect conflict. However, results further indicate that despite the strength of congregations’ religious values, conflict continues because it cannot be avoided in any organisation. Misbehaviour has a positive and significant effect on organisational commitment, as well as affects changes in church commitment. The higher the Misbehaviour, the higher the commitment to make improvements in church governance, organisationally and faithfully. Religious social values have a positive and significant effect on organisational commitment, and will affect changes in church commitment. The higher the religious social values, the higher the organisational commitment of the congregation. Results showed that conflict has a positive and significant effect on organisational commitment and supply chain strategies. Conflict also will affect changes in church commitment. The higher the conflict, the higher the commitment to make improvements in church governance, organisationally and faithfully.